The Effect of Competence and Motivation on the Performance of Non-Civil Servant Government Employees (PPNPN) at the Secretariat General of the House of Representatives of the Republic of Indonesia : English - Bisma Alfaidzi Arandhika; Asropi (Social Science Academic, 2026)
This study aims to analyze the influence of competence and motivation on the performance of Non-Civil Servant Government Employees (PPNPN) within the Secretariat General of the House of Representatives of the Republic of Indonesia. It employs a quantitative approach using a survey method and an explanatory research design. The study population consists of 4,432 PPNPN employees, with a sample of 367 respondents determined using Slovin's formula. Data collection was conducted through questionnaires, observation, documentation, and literature review. Data analysis was performed using SPSS version 25, involving validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that competence has a positive and significant effect on employee performance, with a significance value of 0.000 (< 0.05). Motivation also has a positive and significant effect on employee performance, with a significance value of 0.000 (< 0.05). Simultaneously, competence and motivation significantly influence employee performance, contributing 58.6% to the outcome. This study is significant as it provides insight into the factors affecting PPNPN employee performance, thereby serving as a basis for evaluation to enhance human resource quality and work effectiveness.